Study on Self-maintenance of Clear-air Turbulence - Krzysztof E. Haman (Research Trends and Challenges in Physical Science Vol. 3, 2021)
Clear air turbulence (CAT) has sometimes form of limited patches which are only few hundreds or even tens of meters thick but may extend over many kilometres in horizontal. In certain conditions such patches being once formed by some external mechanism, may create an internal feedback maintaining their existence over longer time. The paper shows an example of such feedback, based on redistribution of Richardson number by turbulent mixing within the patch.